The place of the memory: the education, the interrelationships and the personal collection of Fernando Augusto Albuquerque Mourao - Cruz, Clauber Ribeiro [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
Through the access of Fernando Augusto Albuquerque Mourao collection, this paper aims to present the contributions of this intellectual in so many fields of your studies. Thus, we intend to organize his archives and memory presented in the collection in order to rebuild his career. With the analysis of these personal files, we aim to examine part of the professional and personal paths of this important Brazilian intellectual. Therefore, some moments of his academic and personal paths will be checked, since his connection with the Casa dos Estudantes do Imperio, em Portugal, until the creation of an elemental place to the African studies in Brazil, combined with the international African relations: the Centro de Estudos Africanos, of the Universidade de Sao Paulo.
Keywords: Personal Collection; Students Empire House; Center of African Studies; Collection of African Writers; Fernando Mourao